2006
DOI: 10.1007/s11746-006-1221-z
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of soybean fatty acids by near‐infrared spectroscopy: Linear and nonlinear calibration methods

Abstract: A key element of successful development of new soybean cultivars is availability of inexpensive and rapid methods for measurement of FA in seeds. Published research demonstrated applicability of NIR spectroscopy for FA profiling in oilseeds. The objectives of this study were to investigate the applicability of NIR spectroscopy for measurement of FA in whole soybeans and compare performance of calibration methods. Equations were developed using partial least squares (PLS), artificial neural networks (ANN), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 15 publications
2
45
1
1
Order By: Relevance
“…The electronic nose (sensor responses analyzed by a neural network) achieved success similar to that obtained using the more usual fatty acid analysis by gas chromatography. Similar application in fatty acid analysis of soyabean oil is reported by Kovalenko et al (2006). An artificial neural network model is presented for the prediction of thermal conductivity of food as a function of moisture content, temperature and apparent porosity.…”
Section: Ann For Prediction Of Food Quality Properties and Shelf Lifementioning
confidence: 79%
“…The electronic nose (sensor responses analyzed by a neural network) achieved success similar to that obtained using the more usual fatty acid analysis by gas chromatography. Similar application in fatty acid analysis of soyabean oil is reported by Kovalenko et al (2006). An artificial neural network model is presented for the prediction of thermal conductivity of food as a function of moisture content, temperature and apparent porosity.…”
Section: Ann For Prediction Of Food Quality Properties and Shelf Lifementioning
confidence: 79%
“…They suggested that these NIRs equations have potential for use in screening for unsaturated fatty acid content in soybean seed oil. Kovalenko et al (2006) also reported that NIR equations for total saturates had high predictive ability (r 2 =0.91-0.94), however unsaturated fatty acids showed low predictive abilities, oleic (r 2 =0.76-0.81), linolenic (r 2 =0.73-0.76), and linolenic (r 2 =0.67-0.74). NIR spectroscopy also has been used determine soybean oil quality such as determination of degradation in frying oil (Yildize et al, 2001;Gerde et al, 2007), peroxide value in oxidized soybean oil (Yildiz et al, 2003), and cis and trans content in hydrogenated soybean oil (Li et al, 1999).…”
Section: Applicationsmentioning
confidence: 93%
“…PLS provides a dataset with relevant information and reduced dimensionality; this method eliminates data noise to obtain a more accurate and reproducible calibration 13,26 .…”
Section: Pls Calibration Development and Validationmentioning
confidence: 99%
“…The values of R and RMSEC of the calibration were considered as an indicator in quality evaluation. In general, the larger the values of R and RMSEC are, the more predictive ability of the calibration is obtained 26 .…”
Section: Pls Calibration Development and Validationmentioning
confidence: 99%